Potensi Ekonomi Wisata di Kawasan Perbatasan Desa Sahan Kabupaten Bengkayang - Andani, Meri; Fahruan, Yulyanti; Krint, Kiwa Fliirando; Sampore, Gabriel; Yasmiati, Fransiska Eka; Fernando, Muhammad Iqbal Attalarik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Sahan Village, which is located in the Indonesian border region, has a variety of potential natural resources and economic opportunities that have not been fully exploited. As a village that borders directly with a neighboring country, Sahan Village has the opportunity to market its abundant natural resources such as tourism, agriculture and a variety of local culinary delights. In this case, of course, adequate quality human resources are needed in order to develop the economic potential in Sahan Village. This type of research that uses a participatory approach or Participatory Action Research is a research model that seeks something to connect the research process to the process of social change in improving the community's economy. Economic development is defined as an effort to increase local economic income on the pretext that to become an independent and sustainable region, the region must be able to utilize its resources to the maximum extent possible so as to create added value and a long production chain. The aim of developing tourism economic potential in border areas is increasing local economic income and developing sustainable tourism. Sahan Village, Bengkayang Regency can become one of the villages that can be developed as a tourist village destination that is environmentally friendly, insightful, and can have a positive impact on the community, government and tourists. Community-based ecotourism can create new jobs for the community and improve community welfare as well as provide a positive impact on local communities, environmental and socio-cultural preservation so that it can foster a sense of self-confidence among local residents that develops through ecotourism activities.